Exploring the Lived Experiences of Home-Educating Families with Young Children in the UK: The Untold Stories - Kaili C. Zhang; Lindsay Gibson (MDPI AG, 2024)
Recent trends indicate a significant increase in the number of families opting for home education in the UK, yet research dedicated to this area remains limited. Moreover, there is a notable scarcity of studies focusing on the lived experiences of home-educating families of young children. Amidst this context, a new conceptual framework was developed combining the portraiture approach and the life course theory to study five families with young children in the UK. Semi-structured interviews, observations, and curriculum document analysis were used to gain insights into these families' experiences. The study revealed diverse motivations driving parents to choose home education, including concerns about the traditional education system, a preference for personalized learning, and personal lifestyle choices and ideologies. The research data presented suggests that participants had diverse and dynamic daily routines shaped by their unique educational philosophies. In general, parents consistently sought beneficial opportunities to foster their children's social development. Challenges participants faced included curriculum suitability, financial burdens, and managing dual roles within the home. However, participants viewed these challenges as worthwhile because their main aim of educating their children in a purposeful manner was being met. In line with the theme of parental autonomy in education, parents shared their belief in the freedom for families to educate their children outside traditional schools. They supported flexi-schooling, advocated for accessible resources, the inclusion of home-educated children in assessments, and government funding provision.